Integration of Religious Moderation into the Indonesian Islamic Religious Education Curriculum: Literature Review - Fathunnajih; Sumiarti; Rizki Kurniati; Nur Hamidah; Akhmad Syahbudi (SOSIOEDUKASI, 2025)
This study intends to use content analysis to examine the Islamic Religious Education curriculum and the ways in which moderate religious ideals are incorporated. Incorporating principles like tawassuth (moderation), tasamuh (tolerance), i’tidal (justice), and muwathonah (patriotism) into Islamic Religious Education curricula is becoming more and more crucial in light of rising fears of student radicalism and intolerance. Employing a qualitative library research method, the study critically examines curriculum documents, including syllabi and lesson plans, along with academic literature on Islamic education and religious moderation. The findings reveal that while values of moderation are present in curriculum components particularly in learning objectives and teacher practices their representation tends to be implicit and uneven across different educational institutions. The role of teachers, hidden curriculum, and institutional support is found to significantly influence the internalization of these values. Furthermore, content analysis proves effective in diagnosing both the strengths and gaps in curriculum integration. According to the research, including religious moderation principles into the development and execution of curricula requires a more methodical and quantifiable strategy. This research contributes to strengthening Islamic education's role in fostering inclusive, tolerant, and peaceful learners in Indonesia's pluralistic society